Infrastructure storage Cost: A myth while implementing Enterprise Content Management: Unraveling the Truth behind Infrastructure Storage Cost in Manufacturing Industry (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Infrastructure sizing is very critical for the fast performance of the application in a company wherethousands of users try to access to information simultaneously. Every company wants to harness themaximum out of their investment so accurate sizing is required with projected growth rate.Most of the companies feel that hardware cost takes lion share in it but actually it is a myth.Purpose The purpose of this document is to outline the various cost involved while implementing theEnterprise Content Management in a manufacturing company. Most of the decision making revolvesaround the infrastructure cost while there are other costs which are involved in managing the data insidean organization. To provide good system performance initially and over next five years, this analysis willput some empirical data to reach a conclusion.Designmethodologyapproach The paper presents and analyses an empirical study of an ECM projectwhere SAP is used as leading ERP solution.Findings The findings of the paper include a definition of a process model for sizing infrastructurewhich will help companies to make a right decision while implementing ECM.Research limitationsimplications An overview of sizing infrastructure for ECM system implementationin manufacturing industry where SAP is used as leading ERP solution. Due to data privacy, the clientname is not mentioned.Practical implications This paper is applicable for those organization who are planning to implementECM and Archiving and hovering around storage cost which looks big to them.Originalityvalue There are many articles which deal with Sizing guideline. But this article deals withstorage cost and administration cost of managing the data in manufacturing industry and the mytharound it.